Studies in historical geography and biblical historiography : presented to Zechariah Kallai - Ḳalai, Zekharyah; Galil, Gershon; Weinfeld, Moshe (Supplements to Vetus Testamentum, 2000)
This volume is a collection of studies in historical geography and biblical historiography. It is presented to Professor Zecharia Kallai, one of the leading scholars of historical geography of the Bible, by his students and friends.